2015
DOI: 10.1002/ldr.2418
|View full text |Cite
|
Sign up to set email alerts
|

Rain Use Efficiency, Primary Production and Rainfall Relationships in Desert Rangelands of Tunisia

Abstract: Desert rangelands are characterised by low and highly variable rainfall regime, low forage production and high heterogeneity in the distribution of natural resources. This study was carried out in the desert rangelands of Tunisia to evaluate the response of different rangelands to annual rainfall in terms of aboveground net primary production (ANPP) and rain use efficiency over a 10‐year period (2003–2012). In general, ANPP values were relatively low (123 kg DM ha−1 y−1) but would tend to increase with increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 111 publications
0
28
2
Order By: Relevance
“…The results were in accord with our research. Gamoun [25] thought that understanding how rainfall affects ranching productivity is crucial to predicting the effects of land degradation on the functioning of these ecosystems on desert pastures in Tunisia. Mclendon et al [69] revealed that vegetation preferentially used precipitation-derived soil moisture, even with abundant groundwater.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results were in accord with our research. Gamoun [25] thought that understanding how rainfall affects ranching productivity is crucial to predicting the effects of land degradation on the functioning of these ecosystems on desert pastures in Tunisia. Mclendon et al [69] revealed that vegetation preferentially used precipitation-derived soil moisture, even with abundant groundwater.…”
Section: Discussionmentioning
confidence: 99%
“…Webb et al [24] reported that plant cover affects RUE through alterations in evapotranspiration rate: greater plant cover values lead to greater RUE. Gamoun [25] found that RUE tended to be higher during dry years and lower during wet years on Helianthemum kahiricum (loamy soils) in the desert rangelands of Tunisia. Mi et al [26] also reported that RUE is positively (negatively) correlated with temperature (precipitation) in the Qinghai-Tibetan grassland.…”
Section: Introductionmentioning
confidence: 99%
“…Amendment of organic matter to remediate saline-sodic soils is increasingly considered to be a cost-efficient and more sustainable alternative to the application of expensive inorganic materials [19]. Saline soils generally have low organic matter and nitrogen (N), and in semi-arid and arid regions, the low quality of water and agricultural practices have influenced the sustainability of irrigation systems by reducing soil quality and fertility, causing significant farmland degradation and decline in plant productivity [20]. Increased research is needed to attain agricultural sustainability in such regions [21].…”
Section: Introductionmentioning
confidence: 99%
“…As in all Mediterranean countries, these steppe zones were previously used mainly for grazing and have been subjected to severe pressure from an increasing population, which has slowly stabilized (Floret and Hadjej, 1977). In response to climatic conditions and grazing, the species composition, diversity and abundance, community structure, and plant life forms also changed (Ouled Belgacem et al., 2011, Tarhouni et al., 2015, Gamoun, 2016, Gamoun et al., 2016). Heavy grazing has left Tunisian ecosystems with a homogenized flora consisting only of species that are unpalatable and highly tolerant to herbivory and other forms of disturbance (Gondard et al., 2003, Jauffret and Lavorel, 2003).…”
Section: Rangeland Diversitymentioning
confidence: 99%
“…Sequences of dry years have been a major climatic force in the degradation of rangelands (Verner, 2013). The unreliable distribution of rainfall is an important component which contributes significantly towards the deterioration of rangeland productivity in the dry areas (Floret et al., 1978, Gamoun, 2013, Gamoun, 2014, Gamoun and Hanchi, 2014, Gamoun et al., 2016, Gamoun, 2016). Evidence of this is provided through long term annual rainfall figures in Tunisia, which reveal that desert rangelands are characterized by a dry climate, with hot dry summers and winters and very low levels of precipitation---about 75 mm---from 1997 to 2016 (Fig.…”
Section: Introductionmentioning
confidence: 99%